2023
DOI: 10.3390/app13126932
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Evaluation of Jaw Geometry Reproduction Obtained Via the Use of Selected Orthodontic Materials in Dental Implants and Orthodontics—In Vitro Case Study

Abstract: In this paper, the multiscale analysis of the reproduction accuracy of jaw geometry obtained via the use of selected orthodontic materials is discussed. Impressions were made from two types of impression material. An accuracy assessment of the model geometry mapping was performed using noncontact systems, including a fringe projection optical 3D scanner, computed tomography, and a focus variation microscope. Measurements were made in three modes for comparison, as were the silicone and polyether impression mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
0
0
Order By: Relevance
“…Data analysis showed that deviations were the smallest in the case of silicone and the best fit occurred between the silicone impression and the plaster model. The conducted research confirmed the validity of the assumptions considering the use of multiscale analysis for geometric analysis [12].…”
supporting
confidence: 69%
“…Data analysis showed that deviations were the smallest in the case of silicone and the best fit occurred between the silicone impression and the plaster model. The conducted research confirmed the validity of the assumptions considering the use of multiscale analysis for geometric analysis [12].…”
supporting
confidence: 69%